Both N- and C-terminal domains of galectin-9 are capable of inducing HIV reactivation despite mediating differential immunomodulatory functionalities - Shete, Ashwini; Bhat, Mahalakshmi; Sawant, Jyoti; Deshpande, Supriya (Frontiers in Immunology, 2022)
Background: Shock and kill strategy for HIV cure requires reactivation of latent HIV followed by killing of the reactivated cellular reservoir. Galectin-9, an immunomodulatory protein, is shown to induce HIV reactivation as well as to contribute to non-AIDS and AIDS defining events. The protein is prone to cleavage by inflammatory proteases at its linker region separating N and C terminal carbohydrate binding domains (N and C-CRDs) which differ in their binding specificities. It is important to study the activity of its cleaved as well as uncleaved forms in mediating HIV reactivation and immunomodulation in order to understand their role in HIV pathogenesis and further utilization for shock and kill strategy. Methodology: PBMCs of HIV patients on virally suppressive ART (n=11) were stimulated using 350nM full length, N and C-CRDs of Gal-9. HIV reactivation was determined by analysing gag RNA copies using qPCR using isolated CD4 cells and intracellular P24 staining of PBMCs by flow cytometry. Cytokine responses induced by full length, N and C-CRDs of Gal-9 were also assessed by flow cytometry, luminex and gene expression assays. Changes in T cell helper gene expression pattern after the stimulation were also determined by real time PCR array. Results: Both N and C-CRDs of Galectin-9 induced HIV reactivation in addition to the full length Galectin-9 protein. The two domains elicited higher cytokine responses than the full length protein possibly capable of mediating higher perturbations in immune system if used for HIV reactivation. N-CRD was found to induce development of Treg cells whereas C-CRD inhibited induction of Treg cells. Despite this both the domains elicited IL-10 secretory response although by targeting different CD4 cell phenotypes. Conclusion: N and C-CRDs were found to induce HIV reactivation similar to that of full length protein indicating their possible usefulness in shock and kill strategy. The study indicated an anti-inflammatory role of N-CRD versus proinflammatory properties of C-CRD of Galectin-9 in HIV infection.